The Influence of Political Connections on the Cost of Capital and the Performance of Companies Listed on B3 - Jaison Caetano da Silva; Wlamir Gonçalves Xavier; Cinara Gambirage; Silvio Parodi Oliveira Camilo (BBR: Brazilian Business Review)
The theory holds that in emerging economies, such as the Brazilian one, companies seek to strengthen ties with governmental and institutional actors in order to improve their performance. From the theoretical perspective of the Institutional Theory, this study intends to contribute to previous research, integrating the fields of strategy and finance, investigating the influence of political connections, through campaign donations, the cost of capital and the performance of listed companies on B3. We worked with panel data for data analysis on the period ranging from 1998 to 2016. Our findings do not corroborate the theoretical and intuitive prediction that “crony capitalism” reduces the cost of capital and improves the performance of companies, since we did not obtain empirical evidence that allows affirming that the effect of donations on the cost of capital and the performance of connected companies is different from zero.